Optimization of Precursor Preparation in PSMA-11 Radiolabeling to Obtain a Highly Reproducible Radiochemical Yield - Antonella Iudicello; Stefano Boschi; Pietro Ghedini; Frank Lohr; Stefano Panareo (MDPI AG, 2022)
[68Ga]Ga-PSMA-11 PET/CT plays a pivotal role in the diagnosis and staging of prostate cancer because of its higher sensitivity and detection rate compared with traditional choline PET/CT. A highly reproducible radiochemical yield of the radiopharmaceutical to be used in the clinical routine is an important parameter for planning and optimization of clinical activity. During radiometallation of PSMA-11, the presence of metal ion contaminants in the peptide precursor may cause a decrease in the [68Ga]Ga-PSMA-11 radiochemical yield because of metal ion contaminants competition with gallium-68. To optimize the radiochemical yield of [68Ga]Ga-PSMA-11 radiosynthesis, data obtained by preparing the solution of the PSMA-11 precursor with three different methods (A, B, and C) were compared. Methods A and B consisted of the reconstitution of different quantities of precursor (1000 µg and 30 µg, respectively) to obtain a 1 µg/mL solution. In Method A, the precursor solution was aliquoted and stored frozen, while the precursor solution obtained with Method B was entirely used. Method C consisted of the reconstitution of 1000 µg of precursor taking into account net peptide content as described in European Pharmacopoeia. Radiosynthesis data demonstrated that reconstitution methods B and C gave a consistently higher and reproducible radiochemical yield, highlighting the role of metals and precursor storage conditions on the synthesis performance.